Optimal Enhancement Of Hardness, Hydrophobicity, And Surface Durability Of Pu-Coated Galvanized Material Jis G3302 With Polysilazane Nanomaterial - Irwan Yusril; Arnaldo Muhammad Hans; Arryana Isda Duifa; Ensrodyasmoko Christophorus Chrisangga (E3S Web of Conferences, 2024)
Organic Polysilazane (OPSZ) nano-coatings are applied to the surface of polyurethane car body paint (pu-coated) to improve the hardness, hydrophobicity and durability of the Pu-coated surface. Three types of nano-coatings are used under the brand name Durazane®1500 Rapid cure in the formulas Tutoprom® 3641 and Tutoprom® 3042, along with Nano Coating brand Autoproo under Autoproo. The coating process to the substrate is done using a suede cloth with a wiping method. The coating was done in 1 layer with a dry time of 10 minutes to continue to the second layer. After coating, hardness testing was carried out using pencil hardness and hydrophobicity with Contact Angle measurement. Tests were carried out with curing times of 1 day, seven days, 17 days, and 21 days. To determine the durability, the specimens were left outdoors (exposed to rain and hot sun) for 21 days. Durazane® 1500 Rapid cure in Tutoprom® 3641 and Tutoprom® 3042 formulas increased the hardness up to the H scale, while the Autoproo brand has HB hardness value. Tutoprom® 3641 and Tutoprom® 3042 formulas can cause a taro leaf or hydrophobic effect with a contact angle of 104,5°. From the SEM results, the nano-coating can increase the thickness value and fill the substrate’s pores perfectly, increasing the adhesivity and protecting the pu-coated for a long time. High durability, where after 21 days, the coating still looks glossy and dust-free.